2020
DOI: 10.1007/s00442-019-04590-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to butterfly oviposition partly explain preference–performance relationships on different brassicaceous species

Abstract: The preference-performance hypothesis (PPH) states that herbivorous female insects prefer to oviposit on those host plants that are best for their offspring. Yet, past attempts to show the adaptiveness of host selection decisions by herbivores often failed. Here, we tested the PPH by including often neglected oviposition-induced plant responses, and how they may affect both egg survival and larval weight. We used seven Brassicaceae species of which most are common hosts of two cabbage white butterfly species, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 68 publications
0
24
2
Order By: Relevance
“…Notably, A. cardamines was observed to deposit eggs on A. thaliana in North Sweden where both life cycles briefly overlap 59 . Yet, Pieris eggs have not been reported to induce a leaf necrosis lowering Pieris egg survival on different genotypes of A. thaliana including some Swedish accessions 39,40,60 , neither did we observe a visible necrosis on the tested genotype (Col-0) in our experiments when using P. brassicae egg wash.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Notably, A. cardamines was observed to deposit eggs on A. thaliana in North Sweden where both life cycles briefly overlap 59 . Yet, Pieris eggs have not been reported to induce a leaf necrosis lowering Pieris egg survival on different genotypes of A. thaliana including some Swedish accessions 39,40,60 , neither did we observe a visible necrosis on the tested genotype (Col-0) in our experiments when using P. brassicae egg wash.…”
Section: Discussioncontrasting
confidence: 68%
“…For example, Sinapis alba , did not show HR-like necrosis. However, previous work on the close relative S. arvensis showed that eggs of P. rapae and P. brassicae strongly induced HR-like necrosis 39 . This means that that in some genera there is trait variation between species.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Positive relationships between plant vigour and oviposition preference, abundance and larval performance for other species of lepidopterans have been widely reported (e.g., Freitas et al 1999;Cunningham and Floyd 2006;Han et al 2014;Griese et al 2020). For example, Price and Gerling (2004) found that only vigorously growing shoots of Tamarix nilotica were attacked by the spindle-gall moth Amblypalpis olivierella, and that longer active shoots with more resource available supported more larvae and galls.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of plant hosts by adult insect herbivores and the subsequent development and performance of their offspring is a central issue to understand the evolution of plant-herbivore interactions (Thompson 1988). Ovipositing females should select the quality of the hosts on which larval performance would be greatest to maximize their own fitness, since young instars of herbivorous insects have little or no capacity to move after parental oviposition (Jaenike 1978;Santos et al 2008;Gripenberg et al 2010;Griese et al 2020). Plant quality parameters, such as size, nutritional quality, and defences, have been consistently used to explain the preferences of insect herbivores by certain hosts or organs and consequently their larval performance (De Bruyn et al 2002;Price and Gerling 2004;Heisswolf et al 2005;Santos et al 2008;Han et al 2014;Salgado and Saastamoinen 2019).…”
Section: Introductionmentioning
confidence: 99%